A participação dos serviços no valor adicionado das exportações brasileira: uma análise de insumo-produto - Sene, Lorena Pires (Universidade Federal de São Carlos, 2022)
Services are traditionally considered intangible products, that is, they can be marketed only when incorporated into products from agriculture and/or manufacturing in the form of inputs. However, over the years, it appears that services are increasingly important in the production of economic growth since tertiary activities enable and intensify the increase in interaction between sectors. Considering that exports are a determining factor in national competitiveness and, also, that services are closely linked to changes in the prices of industrial products, this study seeks to investigate the participation of services in the added value of exports through a multisectoral approach, using the input-output analysis methodology, based on data from Brazil in the year 2018. The results point to the Maintenance and Repair Services, Other Service Activities and Transport sectors as key sectors of the services group, highlighting them as important suppliers and demanders for the economy and, also, that the participation of services in exports is substantially higher in added value when compared to their share in the gross value of exports. In this way, it is worth highlighting the importance of understanding the value-added potential of services, because of their relevance in the formulation of public policies aimed at production and trade, which directly and indirectly affect a country's competitiveness.
The participation of services in the value-added of Brazilian exports: an input-output analysis
Keywords: Serviços; Insumo-produto; Valor Adicionado; Exportações; Services; Input-output; Value-added; Exports; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::TEORIA ECONOMICA